Upward nitrate transport by phytoplankton in oceanic waters: balancing nutrient budgets in oligotrophic seas - Villareal, Tracy A; Pilskaln, Cynthia H.; Montoya, Joseph P.; Dennett, Mark (PeerJ PrePrints, 2014)
In oceanic gyres, primary producers are numerically dominated by small (1-5 µm diameter) pro- and eukaryotic cells that primarily utilize recycled nutrients produced by rapid grazing turnover in a highly efficient microbial loop. Continuous losses of nitrogen to depth by sinking, either as single cells, aggregates or fecal pellets, are balanced by both nitrate inputs at the base of the euphotic zone and nitrogen-fixation. This input of N (new nitrogen) to balance export losses (the biological pump) is a fundamental aspect of nitrogen cycling and central to understanding carbon fluxes in the ocean. In the Pacific Ocean, detailed nitrogen budgets at the time-series station HOT require upward transport of nitrate from the nutricline (80-100 m) into the surface layer ( 0-40 m) to balance productivity and export needs. However, concentration gradients are negligible and cannot support the fluxes. Physical processes can inject nitrate into the base of the euphotic zone, but the mechanisms for transporting this nitrate into the surface layer across many 10s of m in highly stratified systems are unknown. In these seas, vertical migration by the very largest 102-103 µm diameter) phytoplankton is common as a survival strategy to obtain nitrogen from sub-euphotic zone depths. This vertical migration is driven by buoyancy changes rather than by flagellated movement and can provide upward nitrogen transport as nitrate (mM concentrations) in the cells. However, the contribution of vertical migration to nitrate transport has been difficult to quantify over the required basin scales. In this study, we use towed optical systems and isotopic tracers to show that migrating diatom (Rhizosolenia) mats are widespread in the N. Pacific Ocean from 140°W to 175°E and together with other migrating phytoplankton (Ethmodiscus, Halosphaera, Pyrocystis, and solitary Rhizosolenia) can mediate time-averaged transport of N (235 µmol N m-2 d-1) equivalent to eddy nitrate injections (242 µmol NO3- m-2 d-1). This upward biotic transport can close nitrate budgets in the upper 250 m of the central Pacific Ocean and together with diazotrophy creates a surface zone where biological nutrient inputs rather than physical processes dominate the new N flux. In addition to these numerically rare large migrators, there is extensive evidence in the literature of ascending behavior in small phytoplankton that contributes to upward flux as well. Although passive downward movement has dominated models of phytoplankton flux, there is now sufficient evidence to require a rethinking of this paradigm. Quantifying these fluxes is a challenge for the future and requires a reexamination of individual phytoplankton sinking rates as well as methods for capturing and enumerating ascending phytoplankton in the sea.
Keywords: vertical migration; diatoms; marine; nitrogen; dinoflagellates; Rhizosolenia; nitrate; biological pump; gyres; mixed layer